2017
DOI: 10.1039/c7ra01597f
|View full text |Cite
|
Sign up to set email alerts
|

Changes in molecular film metallicity with minor modifications of the constitutive quinonoid zwitterions

Abstract: Molecular films of quinonoid zwitterions, of the general formula C 6 H 2 (/O) 2 (/NHR) 2 , have been shown to display electronic properties highly dependent on the nature of the N-substituent R when deposited on gold substrates. The different spacing and organization of the molecules can lead to molecular films with semi-metal or dielectric behavior. With the long term goal to establish how packing effects in the solid state correlate with properties as thin films, we first attempted to identify by X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…For example, while enhancement of S-, Se-, and Te-based polyacenes has been observed, formation of a metallic state by closure of the valence-conduction band gap E g usually requires pressures above 20 GPa, approaching the region where covalent bonds begin to rupture . Various molecular design strategies to reduce Δ E and hence E g have been pursued, the most notable involving the use of internal salts and charge-separated zwitterions, , where the resulting small Δ E can be fine-tuned by substituent and heavy atom effects. With favorable packing motifs, semiconductors capable of metallization at pressures well below 10 GPa have been made …”
Section: Introductionmentioning
confidence: 99%
“…For example, while enhancement of S-, Se-, and Te-based polyacenes has been observed, formation of a metallic state by closure of the valence-conduction band gap E g usually requires pressures above 20 GPa, approaching the region where covalent bonds begin to rupture . Various molecular design strategies to reduce Δ E and hence E g have been pursued, the most notable involving the use of internal salts and charge-separated zwitterions, , where the resulting small Δ E can be fine-tuned by substituent and heavy atom effects. With favorable packing motifs, semiconductors capable of metallization at pressures well below 10 GPa have been made …”
Section: Introductionmentioning
confidence: 99%
“…In parallel, the convenient functionalization of BQIs combined with their large intrinsic dipole (ca. 10 D) made them candidates of choice for the elaboration of molecular films following adsorption or polymerization on metallic surfaces along with interfaces and, more recently, as interlayers in graphene transistors …”
mentioning
confidence: 99%
“…10 D) is deposited between the silicon wafer and the OSC layer. We decided to investigate zwitterionic benzoquinonemonoimine (BQMI) dyes 1–4 ( Scheme 1 ), which have recently been proposed for the creation of molecular films following adsorption [ 20 , 21 , 22 , 23 , 24 ], the polymerization of metallic surfaces [ 25 , 26 , 27 ], for use in interfaces [ 28 , 29 ], and, more recently, as interlayers in graphene transistors [ 30 ]. Lin et al reported a zwitterion-based cathode interlayer in organic photovoltaics, showing that the introduction of such interlayer significantly suppresses trap-assisted recombination in photovoltaics.…”
Section: Introductionmentioning
confidence: 99%